2004
DOI: 10.1021/om040123i
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Electrochemistry of Multiferrocenyl Phosphine and Phosphine Chalcogenide Complexes in Weakly Nucleophilic Electrolytes

Abstract: The anodic electrochemistry of several compounds containing two or three ferrocenyl moieties linked by a phosphine or phosphine chalcogenide group has been studied in dichloromethane containing [NBu 4 ][TFAB], where TFAB is the tetrakis(perfluoroaryl)borate anion, [B(C 6 F 5 ) 4 ] -. In two cases, namely [CpFe(C 5 H 4 )] 3 P (3) and [CpFe(C 5 H 4 )] 2 PdO(Ph) ( 6), the first one-electron-oxidation product is stable on the cyclic voltammetric (CV) time scale and subsequent oxidations at more positive potentials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 25 publications
(51 reference statements)
6
68
0
Order By: Relevance
“…In the cyclic voltammograms of 3b and 3c, irreversible redox processes are observed and are caused by intramolecular electron-transfer processes between the ferrocenyl groups and the phosphorus atom, including follow up reactions. [63,64] This behavior was also found for 3d by Geiger, Barrière, and Kirss [65] and is well studied for 1,1Ј-bis(diphenylphosphanyl)ferrocene [66,67] and diphenylphosphinoferrocene. [65] .…”
Section: J(supporting
confidence: 74%
See 2 more Smart Citations
“…In the cyclic voltammograms of 3b and 3c, irreversible redox processes are observed and are caused by intramolecular electron-transfer processes between the ferrocenyl groups and the phosphorus atom, including follow up reactions. [63,64] This behavior was also found for 3d by Geiger, Barrière, and Kirss [65] and is well studied for 1,1Ј-bis(diphenylphosphanyl)ferrocene [66,67] and diphenylphosphinoferrocene. [65] .…”
Section: J(supporting
confidence: 74%
“…[63,64] This behavior was also found for 3d by Geiger, Barrière, and Kirss [65] and is well studied for 1,1Ј-bis(diphenylphosphanyl)ferrocene [66,67] and diphenylphosphinoferrocene. [65] . For tri-n-butylphosphine (3a), solely phosphorus oxidation is observed, owing to the lack of additional redox-active terminal groups.…”
Section: J(supporting
confidence: 74%
See 1 more Smart Citation
“…[25] The solvent dependence of the electronic and redox chemistry of 1 H was examined in detail to explore the role solvent and other environmental factors play in determining the chemical processes which the oxidised open and closed states undergo. The influence of solvent on the absorption spectra of 1 Ho and 1 Hc, although modest, is apparent (see Supporting Information, Figure S2).…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…However, the irreversibility of wave II implies that a homogeneous chemical process involving this species must take place before reduction. The first hypothesis that was considered to justify this behavior was the reaction between the [MoCp Bz (CO) 2 (PMe 3 )(CH 3 CN)] 2+ and the electrolyte anion PF À 6 [63,64]. It is well documented that BF À 4 may coordinate to molybdenum leading to the formation of zwitterionic complexes [MoCp 0 (CO) 3 (FBF 3 )] (Cp 0 = C 5 H 5 , Cp * , Cp Bz ) [18] and it has also been reported that fluorine abstraction from PF À 6 may be forced by highly acidic metal centers [65][66][67].…”
Section: Electrochemical Studiesmentioning
confidence: 99%